2011
DOI: 10.1097/psy.0b013e3182080d73
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Placebo Analgesia: Event-Related Potentials and Emotional Modulation

Abstract: A placebo response on pain unpleasantness was observed in men only, and reduced stress after placebo administration was observed in males only. Thus, reduced stress may be a mechanism for placebo responses in pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 43 publications
7
83
0
1
Order By: Relevance
“…4). Electroencephalography (EEG) studies have further confirmed that placebo analgesia is associated with reduced amplitudes of event-related potentials to experimental pain stimuli (Wager et al, 2006;Watson et al, 2007;Aslaksen et al, 2011). Evidence from spinal cord forced magnetic resonance imaging (fMRI), which only recently became technically feasible in both humans and animals, has revealed that pain-related activity in the ipsilateral dorsal horn, corresponding to painful stimulation, is substantially reduced under placebo (Eippert et al, 2009b) and rises under expectations of increased pain (nocebo) .…”
Section: A Painmentioning
confidence: 92%
See 1 more Smart Citation
“…4). Electroencephalography (EEG) studies have further confirmed that placebo analgesia is associated with reduced amplitudes of event-related potentials to experimental pain stimuli (Wager et al, 2006;Watson et al, 2007;Aslaksen et al, 2011). Evidence from spinal cord forced magnetic resonance imaging (fMRI), which only recently became technically feasible in both humans and animals, has revealed that pain-related activity in the ipsilateral dorsal horn, corresponding to painful stimulation, is substantially reduced under placebo (Eippert et al, 2009b) and rises under expectations of increased pain (nocebo) .…”
Section: A Painmentioning
confidence: 92%
“…This notion is supported by observations where placebo analgesia was associated with a reduction in subjective stress levels, heart rate, and heart rate variability. The reduction in sympathetic activity appeared to be a factor involved in anticipatory placebo analgesia rather than simply a direct consequence of pain reduction (Aslaksen and Flaten, 2008;Aslaksen et al, 2011). These placebo responses reflected in the heart rate appear to be mediated via the prefrontal cortex, because the impaired connectivity of the prefrontal lobes in Alzheimer patients has been associated with both absent placebo analgesia and a heart rate reduction (Benedetti et al, 2006).…”
Section: F Autonomic Organ Functioningmentioning
confidence: 99%
“…However, experimental studies on placebo analgesia usually reveal higher placebo response rates in male adults (52). To our knowledge, there are only two articles that report analyses of gender differences in the placebo response in children: the review by Evers et al (34) found no gender differences, whereas the other review (53), also focusing on migraine headache, found higher placebo response rates in girls (66.7%) as compared with boys (43.3%).…”
Section: Are the Mediators And Moderators Of The Placebo Effect Similmentioning
confidence: 91%
“…Aslaksen et al [11] recorded stress and arousal in the absence of pain to observe whether stress was reduced by information that a painkiller was administered. Experimental heat pain was induced before, and at 10-15 and at 25-30 min after administration of a painkiller with information that it was a potent painkiller.…”
Section: Do Emotions Modulate the Placebo Response Or Does The Placementioning
confidence: 99%
“…This response bias is a serious problem for the reliability of subjective report, and needs to be considered when recording pain. Especially in the field of placebo analgesia, where response bias has been put forth as an explanation for the reduced pain report after administration of a placebo [9,10], the use of objective methods is especially important, and such methods are being increasingly used [11][12][13].…”
Section: Painmentioning
confidence: 99%